PENAMBAHAN BALLISTIC STRETCHING PADA LATIHAN KNEE TUCK JUMP LEBIH EFEKTIF DIBANDINGKAN LATIHAN KNEE TUCK JUMP TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI PADA PEMAIN VOLI LAKI-LAKI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - I Made Dwi Apri Pramana; I Putu Sutha Nurmawan; I Putu Adiartha Griadhi; Ida Ayu Dewi Wiryanthini (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
Muscle power was defined as the combination between speed and strenght of muscle contraction and enters in the fitness components. Plyometrics exercises can be used to improve the skills of volleyball players. This study was an experimental study using research designs pre test and post test control group design. The sampling technique inthis study with a simple random sampling. The total sample of 20 person so in one group consisted of 10 person. The first group was given additional ballistic stretching on knee tuck jump exercise. The second group was given knee tuck jump exercise. Measurements of leg muscle power using vertical jump test. Normality test p > 0.05 and homogeneitytest p > 0.05. The results showed an increase in leg muscle power in first group amounted to 14.30 cm and in second group an increase of 7.70 cm. Paired samples t-test p value = 0.000 (p <0.05) in first group and p = 0.000 (p < 0.05) in second group. Test increase explosive power leg muscle after exercise in both groups using independent sample t-test obtained first group and second group where p = 0.000 (p <0.05) with an increase in the percentage of 30.95% in the first group and 16.73% in the second group. From the research done can be concluded that the addition of ballisticstretching on knee tuck jump exercise is more effective than knee tuck jump exercise in increasing explosive power leg muscle in male volleyball players Medical Faculty Of Udayana University. Keywords: muscle power, ballistic stretching, knee tuck jump, vertical jump test.